The differential drying shrinkage effect on the concrete surface damage: Experimental and numerical study. (December 2017) - Samouh, Hamza; Rozière, Emmanuel; Loukili, Ahmed
Abstract: This paper aims to study the relation between drying and the development of damage from concrete surface. For that reason, the experimental study aims to measure the internal relative humidity in four different locations during 500 days. In parallel, total shrinkage is monitored for 250 days in different positions of the specimen. Under drying conditions, low differential values are noticed. Higher porosity and pore radius in the specimen edge are observed. It can be explained by the effect of the drying on the cement hydration and the surface microcracks appearance. Based on the experimental results, a model which incorporates the main mechanisms for shrinkage is proposed. The difference between the free shrinkage provided by modeling and the measured strain profile allows determining the evolution of the internal stress by an iterative procedure. Finally, by defining the damaged depth in the specimen as the area where the tensile strength is exceeded, the evolution of this distance is deduced. The development of the damaged depth was very fast as long as the relative humidity was close to 100% in the specimen core with a high differential pore pressure between the center and the drying surface.